Pengaruh Pertumbuhan Penduduk, Tingkat Pengangguran Terbuka, dan Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan di Provinsi Kalimantan Selatan - Khairidah, Noor; Wardhana, Ali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This research topic discusses "The Effect of Population Growth, Open Unemployment Rate, and Economic Growth on Poverty Rates in South Kalimantan Province". This research aims to provide information on the effect of population growth, open unemployment rate, and economic growth on poverty rates in South Kalimantan. This research uses multiple linear regression methods with time series data and uses e-views analysis tools. The findings of this research show that population growth has a significant and positive effect on the poverty rate in South Kalimantan, the open unemployment rate has a significant and positive effect on the poverty rate in South Kalimantan, and economic growth have no significant and negative effect on the poverty rate in South Kalimantan. Then population growth, open unemployment rate, and economic growth together do not have a significant effect on the poverty rate in South Kalimantan.